Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3389/fcvm.2022.994329
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-glucose index and estimated 10-year risk of a first hard cardiovascular event

Abstract: BackgroundWhether Triglyceride-glucose (TyG) index is associated with 10-year risk of a first hard atherosclerotic cardiovascular disease (ASCVD) event in the United States remains unclear.MethodsIn this cross-sectional study, the participants, ranged from 40 to 79 years old, were from the National Health and Nutrition Examination Survey (NHANES) between 1999 and 2018. TyG index was the independent variable and 10-year risk of a first hard ASCVD was the dependent variable. The other variables, such as age, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…For instance, a research conducted in the U.S showed that the relationship between TyG and 10-year risk of ASCVD was stronger in men than women. [37] while the correlation was found to be higher in women than men in another study, in line with our current ndings. [18] Therefore, further exploration is essential for deeper explanation of the gender difference.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, a research conducted in the U.S showed that the relationship between TyG and 10-year risk of ASCVD was stronger in men than women. [37] while the correlation was found to be higher in women than men in another study, in line with our current ndings. [18] Therefore, further exploration is essential for deeper explanation of the gender difference.…”
Section: Discussionsupporting
confidence: 92%
“…Our research demonstrates a signifcant and positive connection between TyG and total CVD, congestive heart failure, myocardial infarction, angina pectoris, and coronary heart disease in the United States population, consistent with previous studies [ 33 , 34 ]. However, current research on TyG and cardiovascular disease has centered on European and Asian populations, with a limited number of studies conducted in the United States [ 35 ]. Following the adjustment of nutritional data covariates such as total energy intake, AHEI, and dietary supplements, our investigation determined that TyG showed a significant and affirmative correlation with total CVD, congestive heart failure, myocardial infarction, angina pectoris, and coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…A joint study of a prospective cohort and the Hong Kong Cohort Study showed that the association between the TyG index and the risk of heart failure events was stronger in women than in men [ 45 ]. In another study of the TyG index and the risk of a first major hard cardiovascular event within ten years, subgroup analyses showed that the above correlation was [β = 3.862 95% CI (3.274, 4.450), < 0.00001] in men and [β = 1.067, 95% CI (0.286, 1.849), = 0.00756] in women) [ 35 ]. Futhermore, our study suggests that associations between TyG, TyG-WC, TyG-WHtR, and TyG-BMI and CVD and CVD mortality was higher in no diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Hua et al. simulated the incidence of ASCVD in participants over the next 10 years and found that the TyG index was associated with an increased risk of ASCVD ( 27 ). Previous studies have demonstrated the promising potential of the TyG index in predicting the risk of CAD ( 28 , 29 ) and the prognosis of adverse cardiovascular events in patients with acute coronary syndrome (ACS) ( 30 , 31 ), stable CAD ( 32 , 33 ), or non-obstructive CAD ( 34 ).…”
Section: Discussionmentioning
confidence: 99%